Analisis Pengaruh Harga Minyak, Kurs, Dan Suku Bunga Terhadap Indeks IDX Financial Periode 2019-2022 Menggunakan Model Autoregressive Distributed Lag (ARDL) - Gunawan, Didik; Nurhafizah, Siti; Kusdiana, Dikdik (Accounting Progress, 2025)
This research aims to analyze the influence of oil prices, exchange rates and interest rates on the IDX financial index for the 2019-2022 period using the autoregressive distributed lag (ARDL) model. This study uses a quantitative approach. The population in this study is daily data from the IDX Financial Index, oil prices, exchange rates and interest rates from January 2019 to December 2022, so the sample in this study is 978 time series data with a sampling technique using a total sampling technique. The data collection method uses documentation published on the sites id.investing.com and www.bi.go.id. Data analysis in this research uses the Autoregressive Distributed Lag method with the help of E-views version 10 software. The results of this research show that in the short and long term world oil prices have a positive and significant effect on the IDX Financial Index. In the short and long term the exchange rate has a negative and significant effect on the IDX Financial Index. Meanwhile, interest rates have no effect on the IDX Financial Index in the short or long term.